Study of natural genetic variation in early fitness traits reveals decoupling between larval and pupal developmental time in drosophila melanogaster - Petino Zappala, María Alejandra; Ortiz, Victoria; Fanara, Juan Jose (Evolutionary biology, 2018)
Characterizing the relationships between genotype and phenotype for developmental adaptive traits is essential to understand the evolutionary dynamics underlying biodiversity. In holometabolous insects, the time to reach the reproductive stage and pupation site preference are two such traits. Here we characterize aspects of the genetic architecture for Developmental Time (decomposed in Larval and Pupal components) and Pupation Height using lines derived from three natural populations of Drosophila melanogaster raised at two temperatures. For all traits, phenotypic differences and variation in plasticity between populations suggest adaptation to the original thermal regimes. However, high variability within populations shows that selection does not exhaust genetic variance for these traits. This could be partly explained by local adaptation, environmental heterogeneity and modifications in the genetic architecture of traits according to environment and ontogenetic stage. Indeed, our results show that the genetic factors affecting Developmental Time and Pupation Height are temperature-specific. Varying relationships between Larval and Pupal Developmental Time between and within populations also suggest stage-specific modifications of genetic architecture for this trait. This flexibility would allow for a somewhat independent evolution of adaptive traits at different environments and life stages, favoring the maintenance of genetic variability and thus sustaining the traits’ evolvabilities.